Improvement of feed efficiency using protected-energy in the ration of ewes - Mathius, I-W; Yulistiani, Dwi; Wina, E; Haryanto, B; Wilson, A; Thalib, A (Indonesian Animal Sciences Society, 2001)
High producing ewes required high amounts of energy, which can not be met through feeding conventional ration. Therefore, supplementing energy should be done, especially protected-energy. The purpose of this study was to determine the effects of additional of protected fat/energy on the consumption of ration and the performance of ewes and lambs. Thirty-four local ewes were randomly allotted to four levels of by-pass energy groups, in which parts of energy content in the concentrate was replaced with rumen-protected fatty acids in the proportion of 0 (R1), 5 (R2), 10 (R3), and 20% (R4). Consumption, nutrient digestibility and animal performance (ewes and lambs) were determined by standard procedures. Results showed that the daily dry matter intake during pregnancy (g/kg BW0.75) did not differ among diet (72.1 + 2.56). The crude fibre intake varied slightly between treatment (P>0.05), those being slightly lower intake on the highest replacement of energy content in concentrate diet (R4). Dry matter digestibility were 52.4 + 0.24, 52.1 + 0.30; 51.8 +0.28; and 51.3 + 0.81 in groups R1, R2, R3, and R4, respectively, which were non-significantly different from each other. These results confirmed that the by-pass energy sources replacements did not affect rumen fermentation. The same tendency was also found for crude protein digestibility (P>0.05) i.e. 60.1; 61.8; 61.2; and 60.2 for R1, R2, R3, and R4 respectively. The average daily gain of ewes during gestation period was affected (P<0.05) by by-pass energy replacement and the effect was linear with increasing by-pass energy replacement. Significant difference was not found in the total birth weight of lambs and among dietary treatments. Lambs growth rate during the first 8 week of lactation was the highest on ewes fed diet containing the highest amount of by-pass energy sources (R4). It can be concluded that by-pass fatty acids can be used in ewesâ ration without affecting rumen fermentation and gave a positive respons to animal performance. Â Key words: By-pass energy, ewes ration, gestation and lactating phase